The Effect of Organizational Capital On Tax Avoidance With Ceo Over Confidence as Moderator - Jumriaty Jusman; Tina Lestari (Return : Study of Management, Economic and Bussines, 2023)
The number of companies reporting losses to avoid taxes increased significantly. This is a concern for the government. The purpose of this study was to examine the effect of organizational capital on tax avoidance with CEO overconfidence as moderator. The samples used in this study are mining companies listed on the Indonesia Stock Exchange (IDX) during 2016-2021 through the purposive sampling method. The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021 that were selected purposively. The year 2016 is used as the base year to measure variables that require data from the previous year. Data is obtained from financial statements published on www.idx.co.id websites and websites of each company. The results of this study confirm that organizational capital can increase tax avoidance whereas The results of this study confirm that organizational capital can increase tax avoidance.